Metasurfaces Enabled by Locally Tailoring Disorder in Phase-Change Materials - Hafermann, Martin; Schoeppe, Philipp; Rensberg, Jura; Ronning, Carsten (ACS Photonics, 2018)
Active optical metasurfaces with dynamic switchable, tunable, and reconfigurable optical functionalities are an emerging field in photonics and optoelectronics. Especially, chalcogenide-based phase-change materials, such as Ge 2 Sb 2 Te 5 (GST), can be fast and repeatedly switched by external stimuli between crystalline and amorphous states, typically accompanied by a tremendous difference of the electronic and photonic properties. Here, we demonstrate that focused ion beam-induced disorder in highly confined regions can transform phase-change materials in active optical metasurfaces by locally adjusting the phase. A careful control of the amount of disorder can locally tailor the effective refractive index in GST films on the nanometer scale, which is highly promising for multilevel switching applications. In contrast to direct laser writing, focused ion beam irradiation enables the fabrication of subwavelength-scaled, planar, nonvolatile, and reconfigurable optical metasurfaces, with pattern sizes clearly below the diffraction limit of common laser light sources.
CRIS-Team Scopus Importer:2023-04-20
Keywords: focused ion irradiation; metasurfaces; phase-change materials; tailoring disorder